Thyroid function and thyroid disorders during pregnancy: a review and care pathway - Delitala, Alessandro P.; Capobianco, Giampiero; Cherchi, Pier Luigi; Dessole, Salvatore; Delitala, Giuseppe (Archives of gynecology and obstetrics, 2019)
Purpose To review the literature on thyroid function and thyroid disorders during pregnancy. Methods A detailed literature research on MEDLINE, Cochrane library, EMBASE, NLH, ClinicalTrials.gov, and Google Scholar databases was done up to January 2018 with restriction to English language about articles regarding thyroid diseases and pregnancy. Results Thyroid hormone deficiencies are known to be detrimental for the development of the fetus. In particular, the function of the central nervous system might be impaired, causing low intelligence quotient, and mental retardation. Overt and subclinical dysfunctions of the thyroid disease should be treated appropriately in pregnancy, aiming to maintain euthyroidism. Thyroxine (T4) replacement therapy should reduce thyrotropin (TSH) concentration to the recently suggested fixed upper limits of 2.5 mU/l (first and second trimester) and 3.0 mU/l (third trimester). Overt hyperthyroidism during pregnancy is relatively uncommon but needs prompt treatment due to the increased risk of preterm delivery, congenital malformations, and fetal death. The use of antithyroid drug (methimazole, propylthiouracil, carbimazole) is the first choice for treating overt hyperthyroidism, although they are not free of side effects. Subclinical hyperthyroidism tends to be asymptomatic and no pharmacological treatment is usually needed. Gestational transient hyperthyroidism is a self-limited non-autoimmune form of hyperthyroidism with negative antibody against TSH receptors, that is related to hCG-induced thyroid hormone secretion. The vast majority of these patients does not require antithyroid therapy, although administration of low doses of β-blocker may by useful in very symptomatic patients. Conclusions Normal maternal thyroid function is essential in pregnancy to avoid adverse maternal and fetal outcomes.